Evaluation on layering effects and adhesive rates of laminated compressed composite panels made from oil palm (Elaeis guineensis) fronds - Izyan Khalid; Othman Sulaiman; Rokiah Hashim; Razak Wahab; Nadiah Jumhuri; Mohd Sukhairi Mat Rasat
The objectives of this study was to evaluate layering effects and adhesive rates of laminated compressed panels manufactured from oil palm (Elaeis guineensis) fronds. Nine types of panels, namely 6-layer,9-layers and 10 layers bonded with adhesive spread rates of 200 g/m,250g/m and 300 g/m were manufactured.The results showed that both bending and internal bonding strenght properties all types of panels increased with increasing number of layers and adhesive amount with an exception of 10-layer panels bonded with 300 g/m. Mechanical properties of such samples were slightly reduced due to their possiblebrittleness as a results of effects of densifications.